Consolidation of bone-like apatite bioceramics by spark plasma sintering of amorphous carbonated calcium phosphate at very low temperature. Issue 4 (April 2018) - Ortali, C.; Julien, I.; Vandenhende, M.; Drouet, C.; Champion, E.
Abstract: Various carbonated calcium phosphate powders were synthesized by aqueous precipitation and ceramics consolidation by spark plasma sintering (SPS) at very low temperature was investigated. The objective was to preserve low crystallinity and avoid material decarbonation. SPS at low temperature only leads to little or no sintering when crystallized powders are used. Amorphous powders are required. In this case, consolidation occurs at temperatures below 150 °C. It is accompanied by crystallization of the amorphous phase into calcium-deficient carbonated apatite Ca10-x-y (PO4 )6-x-y (HPO4 )x (CO3 )y (OH)2-x-y-2z (CO3 )z . The resulting ceramics are microporous and highly cohesive with good mechanical properties (flexural strength = 18 MPa). The sintering mechanism, called "crystal fusion", is based on solid state diffusion of chemical species at the grain boundary and crystal growth within the amorphous particles. These bioceramics that mimic the composition of the bone mineral are expected to have a higher bioreactivity than well crystallized carbonated hydroxyapatite ceramics obtained by conventional sintering.